(untitled) (Research, Society and Development, 2021)
The teaching of cell biology is important because it represents, in addition to memorizing concepts, a step towards scientific interest. However, understanding cellular structures and events that occur at the microscopic level is a challenge for students and teachers. This work aimed to construct an animal eukaryotic cell by students as the theoretical content was approached. For this, first, a problem-situation was presented: How to make scientific and abstract concepts understandable using modeling? The investigative study comprised two data collection instruments: a classroom dialogue and the individual construction of an animal eukaryotic cell. The students performed self-assessment and critical evaluation of the other groups. The built models had different shapes and sizes, respecting the characteristics of the chosen cells. In the present work, the construction of a eukaryotic cell stimulated interest and curiosity, enabling different ways of learning about animal eukaryotic cells. In their reports, the students considered the activity was pleasurable, constructive from the moment they researched the parts of the cell, its structures and functions. This study indicates that the construction of didactic models through investigative activity is important and results in significant learning.